Optimization of a thin-walled composite crash absorber. (October 2020) - Fontana, Marco; Araujo, A.L.; Madeira, J.F.A.
Abstract: This work aims to improve upon the aluminium impact attenuator currently used by the University of Lisbon Formula Student team through a composite solution. The influence of geometrical variations, particularly the use of curved walls, and the number of objectives considered for the optimization are studied. To perform the optimizations, Abaqus is coupled with the Direct Multisearch (DMS) algorithm, the overall performance of the solutions is evaluated and the influence of the introduction of curved walls on the energy absorption capabilities discussed. Off-axis impacts are studied and the effect of curved walls in that situation analysed. An overview of the best configurations achieved is provided and one final configuration is selected. Highlights: Design and optimization of a composite impact absorber to be used in an Formula Student car is presented. The importance of the use of curved-walled structure was evident throughout the present work. Off-axis impacts are studied. To perform the optimizations, Abaqus is coupled with the Direct Multisearch (DMS) algorithm.